Antimicrobial resistance in faecal enterococci and Escherichia coli isolates recovered from Iberian wolf. (8th February 2013) - Gonçalves, A.; Igrejas, G.; Radhouani, H.; Correia, S.; Pacheco, R.; Santos, T.; Monteiro, R.; Guerra, A.; Petrucci‐Fonseca, F.; Brito, F.; Torres, C.; Poeta, P.
Abstract The aim of this study was to report the antimicrobial resistance, the molecular mechanisms associated and the detection of virulence determinants within faecal Enterococcus spp. and Escherichia coli isolates of Iberian wolf. Enterococci (n = 227) and E. coli (n = 195) isolates were obtained from faecal samples of Iberian wolf (Canis lupus signatus). High rates of resistance were detected for tetracycline and erythromycin among the enterococci isolates, and most of resistant isolates harboured the tet(M) and/or tet(L) and erm(B) genes, respectively. The blaTEM, tet(A) and/or tet(B), and aadA or strA‐strB genes were detected among most ampicillin‐, tetracycline‐ or streptomycin‐resistant E. coli isolates, respectively. E. coli isolates were ascribed to phylogroups A (n = 56), B1 (91), B2 (13) and D (35). The occurrence of resistant enterococci and E. coli isolates in the faecal flora of Iberian wolf, including the presence of resistant genes in integrons, and virulence determinants was showed in this study. Iberian wolf might act as reservoir of certain resistance genes that could be spread throughout the environment.